CORPORAL BALANCE IN ELDERLY PEOPLE: THE RELATIONS WITH THE SIGHT (Fiep Bulletin - online, 2014)
The present study was aimed to verify the static balance in elderly people, as well as the influence of sight in this task. Thirty-one subject of both sexes, with average age of 67,42  6,2 years old, corporal weight 694,48  119,78 N and 1,57  0,08 m of stature participate in the study. For the kinetic assessment it was used an AMTI(Advanced Mechanical Technology, Inc) platform of force. The data were collected in the open and closed eye conditions, with the feet positioned in the width of the hip. It was collected six attempts of 30 second  three for each position in a frequency of 100Hz. The corporal balance was analyzed through the amplitude and the center of force displacement in the anterior-posterior and medium-lateral directions.  For the data analysis it was used descriptive statistics and t test for comparison. According to the results found, the conclusion is that the values were different only in the variable center of force amplitude in the anterior-posterior direction when the visual information was manipulated. For the other variables it was not found statistically meaningful differences. Thus, the final conclusion is that the visual information is important for the balance of elderly people.
Keywords: static balance; elderly people